Diagnostic value of aspiration biopsy in breast tumors - Campos R. de C., J. (1953)
We have studied the advantages, limitations and indications of the method of aspiration biopsy in a series of 80 breast tumors. From the results obtained it is concluded that this is a harmless method of great value in the anatomical diagnosis of ulcerated lesions in which biopsy should not be performed section; allows certain pre-operative diagnosis and nonsurgical in advanced cases, the only oprtunidad constitutye anatomical diagnosis. Close collaboration between the oncologist and pathologist, as a fundamental condition for good samples, and to provide proper interpretation of them is indispensable.